PENGGUNAAN MEDIA KARTU HURUF UNTUK MEMAHAMI KONSEP HURUF KAPITAL SISWA KELAS IVSD NEGERI 167 PEKANBARU - Lia Noviarti Handayani; Otang Kurniaman; Zulkifli Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research executed because lowering of understanding of letter concept of capital class student of IV SD Negeri 167 Pekanbaru. From initial test perform only 5 student from 30 student who achieved KKM with the average value 51,83. Purpose of this research is to increase the understanding the concept of capital letter fourth grade SD Negeri 167 Pekanbaru by using a media card letter. Based on the result of this research at the first meeting of the first cycle knowing that teacher’s activity obtained of 55% categorized enough, at the second meeting of the first cycle with the percentage of 60% enough categorized. At the first meeting at the first cycle with the percentage 80% goodness categorized, at the second meeting of the second cycle with the percentage 90% very good categorized. At the student activity obtained of 50% categorized enough, at the second meeting of the first cycle with the percentage of 65% goodness categorized. At the first meeting at the first cycle with the percentage 80% goodness categorized, at the second meeting of the second cycle with the percentage 95% very good categorized. At baseline understanding of student writing capital letters, 4 students understand, 3 students quite understand, and 23 other people do not understand the concept of capital letters. On the basis of scores of students who completed 5 people, while 25 people were not completed, the classical completeness of 16,6% (not finished). At the end cycle repeat the first, student who completed 18, while not complete 12 people with classical completeness 60% (not finished). At the end of the second cycle increased consistency, student who complete 28 people, with classical completeness 90% (finished).Keywords : Card Letter Media, Understand the Consept of Capital Letters